Implementing a Dual Payment Method for Mobile Charging Stations in Urban Areas - Yonda, M Budi Satria; Harpawi, Noptin; Widiasari, Cyntia (SHM Publisher, 2024)
The mobile phone has become the communication device of choice for most people due to its practicality compared to other communication devices. A mobile phone requires electrical energy from its battery to function. Over time, the electrical energy stored in the battery depletes, and the phone needs to be recharged. A frequent problem arises when users are outside without a charger or have difficulty finding a safe power source. To address this issue, this final project proposes a solution: a secure mobile charging station that can be placed in public locations such as stations, hospitals, banks, hotels, malls, restaurants, and other venues. The paid mobile charging station consists of six charging lockers. Each locker is secured with a solenoid lock controlled by a Node MCU ESP32 microcontroller. Payment can be made using either coins or an RFID card. To charge their mobile phones, users must insert coins or swipe an RFID card. Once payment is made, users can charge their phones in the provided lockers for a specified period. System testing demonstrates high reliability, with a 100% success rate in coin validation, accurate RFID balance deductions, and seamless data transmission between the ESP32 and the database. The results indicate that the proposed system is a cost-effective, scalable, and secure solution for providing public mobile charging services in locations such as malls, hospitals, and transportation hubs.